EVOLUTION OF LANGUAGE FAMILIES - Jumanazarova Mehrangiz Joʻrabek qizi (Modern American Journals, 2025)
The evolution of language families is one of the most interesting and complex processes in the history of mankind. Language is the main means of human communication, which plays an important role in the formation of society and culture. Language families, in turn, represent a group of related languages, which, having descended from a common origin, diverged over time and separated into new languages. The evolution of language families is one of the main research areas of linguistics, through which the development, spread and changes of human language are studied.
Keywords: Language, linguistics, grammatical, phonetic and lexical features, culture, computer technologies, methods.